Hematuria in a Patient with Non-malignant Bladder Nodules - Terese S Bergheim; Visal Nga; Andrew C Burg; Bahman Chavoshan (Global Journal of Rare Diseases - Peertechz Publications, 2020)
Introduction: Gross hematuria in adults with resultant anemia is highly concerning for genitourinary malignancy.  However, in rare instances, malakoplakia can mimic such malignancy. Malakoplakia is a benign granulomatous condition with malfunction of the phagolysosomal activity of macrophages and monocytes. This leads to formation of foamy histocytes with intracytoplasmic basophilic inclusions known as Michaelis-Gutmann bodies.  These inclusion bodies are pathognomonic for the condition.    Case presentation:  A 41-year-old female presented with spontaneous gingival bleed and painless gross hematuria for 2 days. Two weeks prior to the current admission she had been hospitalized with gastrointestinal bleed and gross hematuria with symptomatic anemia. The hematuria diminished during treatment with ceftriaxone. She was discharged with a course of cephalexin to treat complicated cystitis. On the subsequent admission, she denied taking any medications. Labs on admission showed Hgb 8.6g/dL, WBC 4.9×109/L (4900/μL, platelets 307×109/L (307×103/μL), INR 1.09, creatinine 61.88μmol/L (0.7mg/dL), calcium 2.17mmol/L (8.7mg/dL). Cystoscopy showed several very abnormal appearing nodules present all over the bladder in a very unusual and abnormal fashion. Frozen section from the biopsy showed no evidence of malignancy but possible fungal infection. Final biopsy result showed malakoplakia, negative stains for acid fast bacilli and fungal organisms, and no evidence of tumor. Urine cultures for bacteria, fungus, acid fast bacilli were negative. Tissue culture grew light Enterococcus faecium, vancomycin resistant (VRE), sensitive to linezolid and quinopristin/dalfopristin, and light Candida glabrata. She was treated presumptively with ceftriaxone but switched to linezolid based on results from tissue cultures. Discussion: The German scientists and physicians Michaelis and Gutmann first described Malakoplakia in 1902. Malakoplakia is a rare condition that most commonly affects the urinary tract and can mimic tumors. It is a benign condition characterized by a granulomatous process consisting of foamy histiocytes with basophilic Michaelis-Gutmann bodies. These basophilic inclusions consist of partially digested bacteria and calcium and iron deposits that result from a defective phagolysosomal activity in the macrophages. It is more commonly reported in patients with immunodeficiencies like HIV or in transplant patients. It is important to obtain a correct pathologic diagnosis in these cases given that it is a benign condition that mimics carcinoma. Treatment consists of a prolonged course of antibiotics. Bethanechol and ascorbic acid appear to improve cure rates.